2017
DOI: 10.1152/japplphysiol.00018.2017
|View full text |Cite
|
Sign up to set email alerts
|

Swimming attenuates d-galactose-induced brain aging via suppressing miR-34a-mediated autophagy impairment and abnormal mitochondrial dynamics

Abstract: microRNAs (miRNAs) have been reported to be involved in many neurodegenerative diseases. To explore the regulatory role of miR-34a in aging-related diseases such as Alzheimer's disease (AD) during exercise intervention, we constructed a rat model with d-galactose (d-gal)-induced oxidative stress and cognitive impairment coupled with dysfunctional autophagy and abnormal mitochondrial dynamics, determined the mitigation of cognitive impairment of d-gal-induced aging rats during swimming intervention, and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 42 publications
4
33
1
Order By: Relevance
“…Therefore, DKK1 plays a key role in influencing cognitive function through Wnt signaling. In addition, Sirt1 plays critical roles in a series of brain functions; as confirmed by one of previous studies with the significant down-regulation of Sirt1 in oxidative stress-induced AD rats and obvious up-regulation of Sirt1 upon 8-week swimming intervention, thereby improving cognitive function (Kou et al, 2017). Due to the cross-talk among DKK-1, Sirt1 and p53, we have also determined the relationships among DKK-1, Sirt1 and p53 in hippocampal tissues of aged rats.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, DKK1 plays a key role in influencing cognitive function through Wnt signaling. In addition, Sirt1 plays critical roles in a series of brain functions; as confirmed by one of previous studies with the significant down-regulation of Sirt1 in oxidative stress-induced AD rats and obvious up-regulation of Sirt1 upon 8-week swimming intervention, thereby improving cognitive function (Kou et al, 2017). Due to the cross-talk among DKK-1, Sirt1 and p53, we have also determined the relationships among DKK-1, Sirt1 and p53 in hippocampal tissues of aged rats.…”
Section: Discussionsupporting
confidence: 58%
“…its suppression may be generally neuroprotective (Horst et al, 2017). Moreover, swimming intervention can delay d-galactoseinduced brain aging in rats via suppressing miR-34a-mediated autophagy impairment and abnormal mitochondrial dynamics (Kou et al, 2017). However, an increase in miR-34a level in the OT group was observed in the present study, indicating that excessive training may activate these maladaptation consequences.…”
Section: Figure 7 | Correlation Between Mir-34a Expression and Bdnf Econtrasting
confidence: 67%
“…Our research team has also found that swimming intervention with a period of 8 weeks can attenuate brain aging in D-galactose-induced AD rats. Mechanically, swimming training down-regulates miR-34a expression in AD rats, which is also confirmed by miR-34a inhibitor in SH-SY5Y cells (78). In normally aged mice, resveratrol treatment can improve learning and memory capacity through down-regulating miR-124/-134, in turn, activating CREB-BDNF signal pathway, which suggests that a resveratrolrich diet may be beneficial for preserving cognitive function in aged individuals (79).…”
Section: Microrna-mediated Aging In Admentioning
confidence: 73%